Oxygen Deficiency Driven Conversion of Polysulfide by Electrocatalysis: MoO3‐x Nanobelts for an Improved Lithium‐Sulfur Battery Cathode. Issue 7 (15th May 2019) - Yi, Yikun; An, Hua; Zhang, Peng; Tian, Xiaolu; Yang, Pu; Liu, Pei; Wang, Te; Qu, Long; Li, Mingtao; Yang, Guidong; Yang, Bolun
Abstract: Despite a high energy density and specific capacity, the commercial implementation of lithium‐sulfur batteries still suffers from a severe polysulfide shuttle. Numerous efforts have been made to confine polysulfide species through physical adsorption and chemical bonding. Nevertheless, polysulfide accumulation is also ascribed to the slow redox kinetics. Herein, we design a kind of MoO3‐x nanobelt with abundant engineered oxygen defects (ODs) on the surface to promote the redox kinetics as a cathode matrix for Li−S batteries. On one hand, engineered ODs exhibit considerable electrocatalytic activity for the conversion of polysulfide in kinetic processes, achieving distinctly improved capacities at large current densities. On the other hand, they enhance the interaction between MoO3 nanobelts and polysulfide molecules from a thermodynamic perspective, leading to an ameliorative cycling stability. This implementation of ODs in Li−S batteries substantially improves electrochemical performances and provides a novel method to introduce engineered defects into matrices for Li−S batteries. Abstract : Engineering vacancy defects in MoO3 nanobelts not only enhances the interaction between the matrix and lithium sulfur compounds, but also promotes electrochemical kinetic activity for the conversion of the polysulfide, providing a promising route to excellent performance in Li−S batteries.